La didáctica de las ciencias en la formación inicial del profesorado: una orientación y un programa teóricamente fundamentados - Furió-Mas, Carles; Gil, D. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
A theoretical foundation of the orientation to be given to the subjects on science/teaching at the initial teacher training stage is attempted. The most recent developments in this field are taken into account.